2023
DOI: 10.1039/d2tb02248f
|View full text |Cite
|
Sign up to set email alerts
|

Development of “smart” drug delivery systems for chemo/PDT synergistic treatment

Abstract: Although chemotherapy and photodynamic therapy (PDT) have been developed for fighting cancer, the complex and heterogeneous nature of tumors makes it difficult for a single therapy to completely inhibit tumor...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 162 publications
0
20
0
Order By: Relevance
“…Currently, various cancer treatments, such as PDT, chemotherapy, radiotherapy, PTT, immunotherapy, etc., have exhibited high anticancer efficacy in laboratory research or clinical practice with great success in suppressing tumor proliferation. ,, However, very often a single treatment modality cannot completely eliminate the whole tumor, and it may be ineffective in preventing cancer metastasis, which is attributed to the complexity, diversity, and heterogeneity of tumors. , To overcome these obstacles of monotherapy, combined therapy, referring to the integration of two or more forms of treatment, has been proposed as an alternative approach to cancer therapy. Indeed, multimodal synergistic therapy can produce “superadditive” effects through cooperative interactions and enhancement among several types of monotherapies, resulting in a stronger therapeutic effect when compared to a single therapy. , Therefore, the current cancer treatment trend has gradually shifted from monotherapy to multimodal treatment for enhanced treatment efficacy. , Most of the multimodal phototherapeutic agents, such as inorganic materials and all-in-one materials, have been developed by integrating different functional components into a nanoplatform. Although these materials can partially satisfy multimodal diagnosis and therapy, there are still some problems such as complexity of the components, low reproducibility, difficulty in processability, and undesired ACQ effects.…”
Section: Combat Diseases: Cancer Theranostics and Bacterial Eliminationmentioning
confidence: 99%
“…Currently, various cancer treatments, such as PDT, chemotherapy, radiotherapy, PTT, immunotherapy, etc., have exhibited high anticancer efficacy in laboratory research or clinical practice with great success in suppressing tumor proliferation. ,, However, very often a single treatment modality cannot completely eliminate the whole tumor, and it may be ineffective in preventing cancer metastasis, which is attributed to the complexity, diversity, and heterogeneity of tumors. , To overcome these obstacles of monotherapy, combined therapy, referring to the integration of two or more forms of treatment, has been proposed as an alternative approach to cancer therapy. Indeed, multimodal synergistic therapy can produce “superadditive” effects through cooperative interactions and enhancement among several types of monotherapies, resulting in a stronger therapeutic effect when compared to a single therapy. , Therefore, the current cancer treatment trend has gradually shifted from monotherapy to multimodal treatment for enhanced treatment efficacy. , Most of the multimodal phototherapeutic agents, such as inorganic materials and all-in-one materials, have been developed by integrating different functional components into a nanoplatform. Although these materials can partially satisfy multimodal diagnosis and therapy, there are still some problems such as complexity of the components, low reproducibility, difficulty in processability, and undesired ACQ effects.…”
Section: Combat Diseases: Cancer Theranostics and Bacterial Eliminationmentioning
confidence: 99%
“…With the advancement of cancer treatments and protocols, there has been a significant increase in survival rates for certain types of cancer. Findings from preclinical and clinical investigations carried out around the world during the past few decades suggest that photodynamic therapy (PDT) is an effective treatment for superficial tumors and diseased tissue. , Photosensitizer (PS) is a critical component for PDT, which utilizes light to activate a PS, producing a chemical reaction and generating reactive oxygen species (ROS) to kill cancer cells. , The second-generation PSs are synthetic compounds primarily based on porphyrins and chlorine structures. , The rigid planes and hydrophobic nature of porphyrin analogues result in aggregation-caused quenching (ACQ) and a decrease in reactive oxygen species (ROS) production. , Polymeric drug delivery systems offer the potential to improve the solubility, bioavailability, and biocompatibility of PSs. However, the microenvironment of solid tumors is characterized by hypoxia caused by the proliferation of cancer cells and the deformation of blood vessels during tumor angiogenesis, which is responsible for the resistance of PDT .…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] Currently, more and more evidences demonstrated that combining photodynamic therapy with chemotherapy could achieve "1 + 1 > 2" synergistic therapy efficacy. [18] After many years of development, supramolecular selfassembly has become the powerful tool to integrate chemotherapy drugs and photosensitizers (PSs) to achieve synergistic photodynamic therapy and chemotherapy. [19][20][21][22] Among them, the host-guest complexation has been the promising construct strategy for this kind of supramolecular nanoplatform.…”
Section: Introductionmentioning
confidence: 99%